Does the surface influence running critical power and W assessment? An in-field study with highly trained trail runners - Jaén-Carrillo, D.; Roche-Seruendo, L. E.; Ruiz-Alias, S. A.; García-Pinillos, F. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: To optimize performance, testing and monitoring are vital for coaches and athletes to understand training adaptations. The critical power (CP) metric, highlighting the highest intensity for maintaining metabolic balance and the excess work capacity (W), stands out for its ease of use through non-invasive methods. Despite its growing popularity for setting training zones, the interchangeability of CP and W across different flat terrains like the athletic track, road, and trail is unclear. This study aims to examine the influence of flat running surfaces on CP and W values among highly trained trail runners, hypothesizing exchangeable values across surfaces. METHODS: Thirteen highly trained trail runners, injury-free and competing internationally, participated in the study. A repeated measures design examined the effect of different flat terrains on Critical Power (CP) and W. Participants underwent three testing sessions on road, track, and groomed trail. Each session included a 9- and 3-min run separated by a 30-min rest. CP and W were determined using a linear model. Participants refrained from vigorous activity 24 hours before each test. Testing conditions were consistent, including environmental factors and footwear. Warm-up included 10 minutes of low-to-moderate intensity running and dynamic exercises. The Borg CR-10 scale assessed perceived effort, and a Stryd power meter measured power output. RESULTS: The analysis using repeated measures ANOVA reveals no significant difference in power output across the 9-minute and 3-minute running intervals conducted on the different flat surfaces, with p-values of 0.387 and 0.624, respectively. In addition, critical power (CP) values, both in absolute terms (watts) and relative terms (w/kg), did not differ significantly across terrains (p = 0.541 and p = 0.583, respectively). Furthermore, the analysis showed no significant difference in W` (p = 0.743). The perceived exertion, measured by the Borg CR-10 scale, was similarly reported to be consistent immediately after the completion of the 9-minute (p > 0.147) and the 3-minute (p > 0.066) running bouts on each terrain. CONCLUSION: This study is aimed at evaluating the influence of flat running surfaces (athletic track, road, and trail) on running CP and W` in highly trained trail runners. The results revealed that the CP and W` determined on the three different flat running surfaces are similar, showing no significant differences between the values. This offers coaches and athletes the opportunity to use any of these flat surfaces to complete a running CP test and extrapolate the value to training sessions to the two other flat surfaces here evaluated. Similarly, coaches and athletes may be confident when determining the W` on any of the three flat surfaces here reported.